A study on the determinants of capital structure in developing countries - Abdelfattah, Adham Hesham (AUC Knowledge Fountain, 2020)
This paper studies determinants of the capital structure of publicly listed non-financial companies in the emerging market countries, mainly Brazil, China, Greece, Hungary, India, Indonesia, Mexico, Philippines, South Africa and South Korea covering a wide range of data from diverse sectors excluding financials. The analysis is based on panel data estimations for a sample of annual observations from companies traded on the stock exchanges of the developing countries during 11 years (2008-2018). Selection criteria for companies will be through the availability of the data. Explanatory variables are categorized into company specific factors as well as macro-factors. The factors used in the study are as follows: profitability, firm size, tangibility, liquidity, asset growth, earnings volatility, effective tax rate and non-debt tax shields. While macro specific factors include stock market capitalization as a percentage of GDP, inflation rate, GDP growth rate and Lending interest rate announced by the central bank of each emerging economy whereby the macro factors are used as we are studying the determinants of capital structure for companies in ten different countries. In the model conducted, I will employ the panel data method to assess the effect of the independent variables that were previously tested on the capital structure (i.e. total leverage) of companies operating in developing countries.